PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (Studi Pelanggan Kartu 4G LTE Indosat di Wilayah Semarang) - Fajar Irianto, 12.05.51.0058 (Students Journal of Economic and Management, 2016)
Increasing competition in the business world telecommunications field, the companies using the opportunity or market opportunities through efforts to improve and promote the quality of service and trust that good, it can cause a consumer satisfaction and loyalty. This study aimed to analyze the impact of service quality and trust on consumer satisfaction and consumer loyalty. The population in this study are all consumers Indosat Card 4G LTE in Semarang region which is not known for certain. Samples taken a number of 100 people and the technique used is purposive sampling. Statistical analysis was conducted on the multiple linear regression and hypothesis testing. Based on the results of data analysis can be concluded; (1) There is a positive and significant influence between service quality to consumer satisfaction, (2) There is a significant positive effect of trust on consumer satisfaction, (3) There is a positive and significant impact of service quality on consumer loyalty, (4) There is a positive effect and significant correlation between trust in consumer loyalty, (5) There is a positive and significant impact of consumer satisfaction on consumer loyalty Keywords: Service Quality, Trust, Consumer Satisfaction, Consumer Loyalty